FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KUALITAS AUDIT (Studi Pada Kantor Akuntan Publik di Jawa Tengah) - Azki Apriliani, 15.05.52.0008; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This study aimed to examine the effect of competency, independence, time pressure, ethics of auditors, due professional care and accountability directly influence the auditor on audit quality. The population in this study were all auditors working at the Public Accountant Office in Central Java. Sampling in this study was conducted using Judgment Sampling techniques and the number of samples was 75 respondents. The primary data collection method used is the questionnaire method. Data were analyzed using multiple linear regression models. The results of the study indicate that the auditor's competence and ethics variables have a significant positive effect on audit quality. time pressure variables have a significant negative effect on audit quality. the independence variable, due professional care and accountability did not have a significant effect on audit quality.